Factors influencing modern contraceptive use among rural married women of reproductive age in Myanmar - Soe, Myint Moh; Sirichotiratana, Nithat; Hong, Seo Ah; Wongsin, Utoomporn; Prutipinyo, Chardsumon (Intelektual Pustaka Media Utama, 2025)
This study aimed to identify factors associated with the use of modern contraceptive service among rural married women of reproductive age in Myanmar. A cross-sectional quantitative study was conducted among 648 married women aged 18-49 years (4 townships with the lowest contraceptive prevalence (n=316) and 4 townships with the highest prevalence (n=332). This study found that women in townships with low prevalence of modern contraceptive use were more likely to be illiterate and manual workers or farmers, to have lower education and no regular income, other religions than Buddhism, and higher number of family members and children, compared to those with high prevalence. In addition, they responded negatively to the accessibility, availability, affordability and acceptability of contraceptive services, and lower satisfaction with the services. This study suggests that the Myanmar government should promote contraceptive services more aggressively for women of reproductive age in rural areas that reflect ethnic minority cultures.